Comparative study of echocardiography and electrocardiography criteria for detecting left ventricular hypertrophy in hypertensive patients - Golla, Abhishek; V. S., Ramkumar; P., Ashok Kumar; S., Ravindranath; Ramaiah, Indira; N., Veena; Gurala, Rajashekar R.; Hussain, Kazi Jawad; Adithya, Vikram (International Journal of Research in Medical Sciences, 2021)
Background: The study aimed to compare seven different electrocardiogram (LVH) criteria for diagnosing left ventricular hypertrophy (LVH) with echocardiogram as diagnostic standard in hypertensive patients. Methods: This was a hospital-based, cross-sectional study conducted in out-patient department and at medical wards of a tertiary care hospital at Bangalore. The study was carried out for a total duration of 12 months. All hypertensive patients underwent examination for prevalence of LVH using echocardiogram and ECG. Seven different ECG criteria were applied to diagnose the presence of LVH. Then the specificity, sensitivity, kappa measurement value, positive predictive value and negative predictive value for all criteria was calculated subsequently. Results: Out of the 100 patients studied, 34 had LVH as diagnosed by echocardiography. Sokolow-Lyon criteria had a sensitivity of 35% and specificity of 94%. Cornell voltage had a sensitivity of 26% and specificity of 95%. Modified Cornell voltage had a sensitivity of32% and specificity of 94%. Framingham adjusted Cornell voltage, Minnesota code and Cornell product had a sensitivity of 23.5% and specificity of 98.4%. Framingham score had a sensitivity of 38% and specificity of 95.4%. Conclusions: It can be concluded that among all the different criteria used in the study, Framingham score showed better sensitivity compared to others. In the evaluation of hypertensive patients for LVH, the role of ECG with all the commonly used criteria is of limited value and echocardiography is the method of choice.